Características morfo-fisiológicas de las raíces en frijoles (Phaseolus vulgaris y Vigna sinensis) - Chávez Leandro, A. (IICA, San José (Costa Rica), 2014)
Tesis (Mag. Sc.) -- IICA, San José (Costa Rica), 1973